Tanggungjawab Pemberitaan Pers dalam Perspektif Teori Keadilan dan Teori Sistem Sosial - Susanto, Joko; Irawan, Irawan; Ilmanta, Rinanda Asrian; Rahma, Dhiny Ligia; Effendi, Sasetya Bayu (LANCAH: Jurnal Inovasi dan Tren, 2024)
This study aims to analyze the role and responsibility of the mass media in considering aspects of justice and social system theory. This study adopts a qualitative approach using literature analysis and case study methods to explore how the principle of justice and social system theory affect journalistic responsibility in media reporting. The results of the article show that the mass media has an important role in ensuring justice in presenting information to the public. The responsibility of the press from a justice perspective involves presenting accurate, balanced, and non-discriminatory information. Meanwhile, social system theory views the media as an integral part of society that must be responsible for shaping public opinion and fighting for social justice. The conclusion of this study is that the responsibility of the press from a justice perspective and social system theory cannot be separated. The mass media has a great influence in shaping the attitudes and values ​​of society, so it is important for them to consider aspects of justice and social systems in their reporting. The implications of this study can provide guidance for more responsible journalistic practices that support social justice.